Strategi Guru Pendidikan Agama Kristen dalam Meningkatkan Minat Belajar Siswa di Kelas IV SD Negeri Handaka Sumba Timur - Giawa, Hasan Nadir; Lunga, Diani Tenga (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This study aims to identify and analyze the factors contributing to the low learning interest of students in Christian Religious Education in Grade IV at SD Negeri Handaka, East Sumba. The background of this research stems from the phenomenon of many students showing a lack of interest in participating in the learning process, which leads to low classroom participation and suboptimal academic achievement. This issue is concerning because Christian Religious Education is not only intended to transfer religious knowledge but also to build character and instill spiritual values in students. This research employs a descriptive qualitative approach, using observation, in-depth interviews with teachers and students, and documentation as data collection techniques. The findings reveal several key factors affecting students' low interest in learning. First, the lack of positive interaction between teachers and students leads to ineffective communication and students feeling neglected. Second, teachers’ inability to effectively use educational technology results in monotonous and conventional learning experiences. Third, the lack of varied teaching strategies fails to actively engage students. Fourth, the limited availability of learning media and tools, such as visual aids or digital devices, becomes a significant obstacle. Additionally, poor time management in classroom activities contributes to students’ boredom and disengagement. These findings highlight the need for concrete efforts from various stakeholders. Teachers must receive training in using technology-based teaching tools and in developing engaging, interactive teaching strategies. Strengthening interpersonal relationships between teachers and students is also crucial for creating a supportive and motivating learning environment. By applying contextual and constructivist-based learning approaches, it is expected that students will become more motivated and enthusiastic in learning. The implications of this study are expected to serve as a reference for teachers, schools, and policymakers to improve the quality of Christian Religious Education, making it more relevant, interactive, and enjoyable for students.